2017
DOI: 10.1016/j.jped.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characterization of neonatal skin disorders in the first 72 h of life

Abstract: Dermatological findings are frequent during the first days of life and some of them characterize the newborn's skin. Mixed-race newborns and those whose mothers had some gestational risk factor had more dermatological findings. The gestational age, newborn's ethnicity, gender, Apgar at the first and fifth minutes of life, type of delivery, and seasonality influenced the presence of specific neonatal dermatological findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 19 publications
1
24
5
1
Order By: Relevance
“…Our observations would support a hypothesis in which disruption of venous return due to increased intraabdominal pressure affects the skin microcirculation and leads to the appearance of telangiectasia. The lesions we observed are not described in articles concerning cutaneous abnormalities 2 or vascular phenomenon of the newborn. [3][4][5] The bilateral character, absence of vasoconstrictive halo, non-congenital nature, and rapid resolution rule out alternative diagnoses such as infantile hemangiomas with minimal or arrested growth 6 or capillary malformations.…”
Section: Ta B L E 1 Characteristics Of 20 Cases Of Transient Abdominal Telangiectasia Of the Newborncontrasting
confidence: 56%
“…Our observations would support a hypothesis in which disruption of venous return due to increased intraabdominal pressure affects the skin microcirculation and leads to the appearance of telangiectasia. The lesions we observed are not described in articles concerning cutaneous abnormalities 2 or vascular phenomenon of the newborn. [3][4][5] The bilateral character, absence of vasoconstrictive halo, non-congenital nature, and rapid resolution rule out alternative diagnoses such as infantile hemangiomas with minimal or arrested growth 6 or capillary malformations.…”
Section: Ta B L E 1 Characteristics Of 20 Cases Of Transient Abdominal Telangiectasia Of the Newborncontrasting
confidence: 56%
“…Our study found that the type and prevalence of neonatal diseases are closely related to gender, gestational age, patient sources, delivery methods, and birth weight. The prevalence of most diseases in males was higher than in females (22)(23)(24). The analysis indicated a statistically significant difference between the patient sources.…”
Section: Discussionmentioning
confidence: 82%
“…The results showed that the proportion of males and females in each gestational age group was similar in inborn/outborn newborns. It was worth noting that gender had significant effect on neonatal prevalence, with males had higher prevalence than females (22)(23)(24). This demonstrates that although males accounted for more resources, there was no gender bias in treatment and referral.…”
Section: Discussionmentioning
confidence: 89%
“…Although common, parents can be reassured that the overwhelming majority of such findings are benign. Several prospective studies conducted in the United States and other countries also report a higher prevalence of newborn skin findings 4-13 (Table 3). The difference may be due to differences in methodologies, as the other studies were prospective compared with our retrospective design based on chart review.…”
Section: Discussionmentioning
confidence: 93%